Analysis of social stereotypes formed among residents of the countries of the Greater Altai and Central Asia by media publications on the Turkic subjects - Ахметова, Л.С. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
. The objective of this study is to designate and identify real, relevant today stereotypes, formed and continuing to develop with the help of media messages, as well as, based on the results obtained, the definition and interpretation of these stereotypes, the designation of possible methods to combat their occurrence and spread. . The relevance of the work is due to the current cultural, media and geopolitical situation, the current information wars and the low level of media literacy of consumers of Russian-language content and, as a result, the easy perception of imposed stereotypes as distorted and simplified images of social groups and states. The purpose of the study is to spread the understanding of the need to develop the level of media literacy as part of the process of mutual cultural, educational and scientific integration between the inhabitants of the countries of the Greater Altai and Central Asia. Studied various, positive, negative, neutral stereotypes formed by famous people, the media, analyzed the attitude towards stereotypes in society. General tendencies are found in the processes of stereotyping in relation to social groups in Western countries, the Russian Federation and the Republic of Kazakhstan. Since the consequence of the emergence of social stereotypes is a direct impact on the image of states and social or ethnic groups, the need to study and correct the work of the media in this direction is noted. The reasons for the need to increase the level of media literacy among the population, as well as the importance of continuing to work on the development of scientific and cultural cooperation between the countries of the Greater Altai, including in the field of journalism and public relations for the most high-quality and wide coverage of their activities among the population, are indicated.